PERAN GURU DALAM MENUMBUHKEMBANGKAN KEMANDIRNAN BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR MELALUI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA - Juraidah Juraidah; Agung Hartoyo (STKIP Persada Khatulistiwa Sintang, 2022)
Independent learning and critical thinking skills are part of the competencies that are expected to realize the profile of Pancasila students. The teacher as the owner of the learning scenario has a central role in developing these competencies. This study aims to determine the role of teachers in developing independent learning and critical thinking skills of elementary school students through a project to strengthen the profile of Pancasila students. This study uses a literature study method by collecting several journals, articles, books, and previous research results that are in accordance with the research problem. The findings in the data collection process were documented and then analyzed and presented descriptively. The results of this study include 1) the value of teachers as agents of change for the realization of the Pancasila Student Profile, including the values of being independent, reflective, collaborative, innovative, and pro-student, 2) Independence and critical thinking are part of the Pancasila Student Profile which is developed through The Pancasila Student Profile Strengthening Project, where the teacher's role in the project is as a project planner, facilitator, mentor, resource person, supervision, consultation, and moderator. The results of this study are expected to increase teachers' understanding of values and their role in developing students' independence and critical thinking in the project of strengthening the profile of Pancasila students.